Grammar dimensions - Parulis, Gene (Heinle & Heinle Publishers, 2000)
Through clear and comprehensive grammar explanations, extensive practice exercises, and lively communicative activities, Grammar Dimensions provides students with the language skills they need to communicate accurately, meaningfully, and appropriately.